2020
DOI: 10.3390/ijerph17062108
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Individual Factors, eHealth Literacy, and Health Behaviors among College Students

Abstract: Background: This study aimed to investigate the associations between individual factors, electronic health (eHealth) literacy, dietary behaviors, and exercise habits in college students, as well as the moderating effect of gender on the above target behaviors. Methods: A pen-and-paper questionnaire with a stratified sampling method was used to collect data, and at least 100 students from each stratum were determined to be used for the official sample in this study. Finally, 674 students completed the survey. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 42 publications
6
31
0
4
Order By: Relevance
“…The preferred form of intake among majority of the DS users was pill (45%), but for unknown reason, a significantly high proportion of males preferred powder form for DS intake than females (15.2% vs. 2.3%). Consistent with some other studies [50], the findings in this study favor gender-specific intervention programs for adolescents to instill knowledge on correct and wise usage of DS. Moreover, a risk of misuse of DS among children and adolescents [51] warrant educational intervention for correct and wise usage and better public health.…”
Section: Discussionsupporting
confidence: 91%
“…The preferred form of intake among majority of the DS users was pill (45%), but for unknown reason, a significantly high proportion of males preferred powder form for DS intake than females (15.2% vs. 2.3%). Consistent with some other studies [50], the findings in this study favor gender-specific intervention programs for adolescents to instill knowledge on correct and wise usage of DS. Moreover, a risk of misuse of DS among children and adolescents [51] warrant educational intervention for correct and wise usage and better public health.…”
Section: Discussionsupporting
confidence: 91%
“…It is shown that e-health literacy could negatively moderate the indirect effect of affective responses on cyberchondria ( Zheng et al, 2020 ). Some studies have noted that people with high e-health literacy are able to understand the information that they find on the internet, verify the veracity of the information, and use this information to promote health behaviors ( Huang et al, 2020 ). They might avoid excessive online health searches, although they are anxious about their health status ( Zheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lower education and health literacy have been linked to poorer health behaviors and poorer treatment adherence in medical settings (Friis et al, 2016; Huang et al, 2020). Presently, a small body of research suggests that individuals with lower education or health literacy may more strongly benefit from health-related behavior-change interventions compared to those with higher education and health literacy (Dominick et al, 2015; Gans et al, 2009; Rothman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is a construct that includes health knowledge as well as the ability to acquire, understand, and appropriately apply health knowledge in a way that prevents disease (Hansen et al, 2015). Prior research indicates that poor health literacy is associated with poorer health outcomes and exercise habits, lower adherence to treatment plans, unhealthy diets and increased risk of dementia (Friis et al, 2016; Huang et al, 2020; Miller, 2016; Oliveira et al, 2019; Park et al, 2017). However, health literacy is not static; health-literacy interventions have been shown to improve health literacy and treatment adherence (Berkman et al, 2011; Miller, 2016).…”
Section: Prior Interventionsmentioning
confidence: 99%